Wireless internet : 12th EAI International Conference, WiCON 2019, TaiChung, Taiwan, November 26-27, 2019, Proceedings /: 12th EAI International Conference, WiCON 2019, TaiChung, Taiwan, November 26-27, 2019, Proceedings. (2020) - Unknown
No abstract available